On the first ruin moment for a modified risk process with immediate reflection - Gusak, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
For a modified risk process with immediate reflection downward, we establish relations for an integral transformation of its characteristic function and the corresponding transformation of the limit distribution of the considered process under ergodicity conditions. The distribution is obtained for the first ruin moment of the introduced risk process.